Evaluation of the protective effect of Omega-7 against Methotrexate Genotoxicity in bone marrow Cells of Mice - Hasani, Zahraa H.; Hassan, Ali F. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: A substance that can affect DNA or chromosomes is defined as a genotoxin. DNA damage in a somatic cell may result in a somatic mutation (cancer). In contrast, damage to a germ cell (germline mutation) may result in a heritable changed characteristic.Omega-7 is a non-essential monounsaturated free fatty acid with anti-inflammatory, anti-obesity, and antidiabetic effects. Objectives: Evaluation of the possible protective effects of omega seven against methotrexate genotoxicity. Method: Two major equal groups were obtained from seventy mice, and five subgroups (each of seven) were created from these groups as follows: Group I received liquid paraffin orally for seven successive days. Group II: received liquid paraffin orally for seven successive days, followed by a single intraperitoneal dose of methotrexate (20 mg/kg) on the eighth day. Group III: received omega-7 (50mg/kg) orally for seven successive days, followed by a single intraperitoneal dose of methotrexate (20 mg/kg) on the eighth day. Group IV: received omega-7 (100mg/kg) orally for seven successive days, followed by a single intraperitoneal dose of methotrexate (20 mg/kg) on the eighth day. Group V: received omega-7 (100mg/kg) orally for seven successive days. The first major group was intraperitoneally injected with 1mg/kg colchicine, and then after two hours, all mice were killed by spinal dislocation. Bone marrow cells from the first major group were used to measure the mitotic index and chromosomal aberrations, and bone marrow cell of the second group was used to measure the appearance of the micronucleus. Statistical Package for Social Sciences (SPSS) and ANOVA test were used to compare groups. Results: Treatment of mice with omega-7 led to a significant decline in chromosomal aberration and micronucleus aberrance with a significant elevation of the mitotic index. Conclusion: Omega-7 has been shown to have a protective role against methotrexate genotoxicity. Received: April, 2023 Accepted: July, 2023 Published: Jan.2024